Music Therapy and Story Telling: Nursing Interventions to Improve Sleep in Hospitalized Children. (29th March 2019) - Anggerainy, Shinta Widiastuty; Wanda, Dessie; Nurhaeni, Nani
ABSTRACT: Music therapy and story telling are examples of nursing interventions that facilitate the management of sleep disturbance in children. However, only a few studies have addressed the effectiveness of music therapy and storytelling on hospitalized children. This study aimed to examine the effect of music therapy and storytelling on sleep disturbance in hospitalized children for various medical conditions. This recent study was a preliminary study that included two intervention groups without a control group. This study involved 31 children with ages ranging from infancy to school age who were assigned to a 3-day music therapy or storytelling intervention group. Group 1 received music therapy ( n = 16) and group 2 was provided with story telling ( n = 15). Data collection was conducted from February through April 2018 in an infectious diseases ward of a hospital in Jakarta. Data related to sleep disturbance in children was collected using GATIA scale, an instrument measuring a sleep disturbance scale. Study results showed a significant change in the average of sleep disturbance scale score in both group 1 and group 2 ( p < α ; α = .05) which demonstrate that both music therapy and story telling improved scores on a sleep disturbance scale in hospitalized children. Music therapy and story telling were equally effective in managing sleep disturbance in children. Music therapy and story telling are safe, cheap, and convenient interventions that can improve the quality of sleep in children during hospitalization.